291 The role of whole exome sequencing in management of recurrent low grade serous ovarian carcinoma – a small case series. (18th September 2019) - Moran, B; Wilkinson, M; Das, S; Loftus, B; Mulligan, N; Duffy, A; Kelly, C; Higgins, M; Boyd, W; Walsh, T; McVey, R; Brennan, D
Abstract : Objectives: Treatment options for recurrent low grade serous ovarian carcinoma (LGSOC) are limited. Herein we describe the potential utility of next generation sequencing in identifying therapeutic targets for this rare tumour. Methods: 3 patients were included in this study. DNA was extracted from ten FFPE tumour samples (5 from primary surgery and 5 from recurrences) and whole blood. Whole exomes sequencing (WES) was performed on Illumina's NextSeq platform to a depth of at least 10X. Sequence data were trimmed, aligned and single nucleotide variants and copy number alterations were called. Results: All samples were microstatellite stable, 2 of the 3 patients had an elevated tumour mutational burden(TMB) (defined as >10 mutations/Mb). In the patient with low TMB we identified a class 3 'kinase-dead' BRAF variant, D594G with concordant near-whole chromosome 1 amplification, covering the NRAS proto-oncogene. Single gene testing confirmed wild type EGFR and KRAS. This lady did not respond to a trametinib. The second case identified a pathogenic NBN R43* mutation with associated non pathogenic mutations in other DNA damage response genes. This patient who had previously declined cytotoxic chemotherapy has had a partial response to platinum based chemotherapy. The third patient did not have a targetable mutation but is awaiting PD-L1 testing. Conclusions: WES may be helpful in refractory LGSOC when standard treatment options have been exhausted. Two of our patients had an elevated TMB suggesting that the efficacy of immunotherapy in LGSOC should be investigated.